Private Armies in Contemporary International Politics - Ahmedi, Bujar; MSc. Besian Ahmeti (European Journal of Multidisciplinary Studies, 2018)
The use of mercenaries has been historically a constant phenomenon till almost the end of the XX century, when their activities were criminalized by the international community. Although the age-old profession of being a mercenary may be as old as the history of warfare itself, we are perhaps witnessing a ‘golden age’ for the soldier of fortune. Since the end of the Cold War, there has been a proliferation of mercenary activity across the globe. Today’s modern mercenary cohorts, the ‘private military companies’ (PMCs) that pursue their services the world over, have become big business. Since 2004, the total net worth of publically traded PMCs, excluding some less legitimate enterprises, exceeded -100bn globally. Despite the prolonged economic malaise post-2008, the private security sector has maintained an impressive upward pattern of growth. This emergence of the PMC as a key security actor within conflicts and regions of instability around the world has strengthened the age-old academic interest in the affairs of the mercenary.